Developing your communication skills in social work - Beesley, Paula, author (SAGE, 2018)
What is communication and why is it important? Our ability to communicate is central to everyday life and an essential skill in social work. This easy-to-read book offers a step-by-step guide to developing effective communication skills with a diverse range of service users and professionals. It is the perfect guide to help manage different communication skills in different settings, and more importantly, encourage students to continually reflect and develop these skills.